SURVEY ON THE NEED FOR APPLICATION OF AURICULAR ACUPUNCTURE IN TREATMENT AT VINH LONG PROVINCIAL TRADITIONAL MEDICINE HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Objective: To assess the demand for auricular acupuncture among patients and the perceived need for applying this technique in treatment among traditional medicine physicians at Vinh Long Provincial Traditional Medicine Hospital Methods: A descriptive cross-sectional study was conducted on 385 patients and 21 traditional medicine physicians at Vinh Long Provincial Traditional Medicine Hospital from November 2023 to May 2024. Data were collected using a structured questionnaire based on the Health Belief Model (HBM) on a five-point Likert scale and analyzed using Stata 14.2.Results: A total of 78.2% of patients expressed a desire to receive auricular acupuncture, while 81% of physicians indicated willingness to apply the technique in clinical practice. The main barriers reported by patients included: the method not yet implemented in the hospital (60%), concerns about cost, and mild discomfort. Most physicians (61.9%) believed that the hospital lacked sufficient equipment for implementation; however, two-thirds stated that they would be confident in performing auricular acupuncture if provided with adequate training and professional support.Conclusion: Both patients and healthcare staff at Vinh Long Provincial Traditional Medicine Hospital demonstrated a high demand for the use and implementation of auricular acupuncture. Strengthening training activities, technical workshops, and infrastructure investment is essential to establishing auricular acupuncture as a routine therapeutic technique in the hospital.
Keywords: Auricular acupuncture, demand, traditional medicine, Health Belief Model.